Uma introdução ao movimento do neoateísmo : definições e metateses - Santos, Valmor Ferreira (2016)
This master's thesis in religious studies titled An Introduction to movement of New Atheism: definitions and metatheses aims to present an introduction to very basic problems New Atheism (NAT). The NAT is commonly associated to four people, namely Sam Harris, Richard Dawkins, Daniel Dennett and Christopher Hitchens are considered the fathers of this set of ideas about religion. The object of this dissertation is not primarily the theses sustained by these intellectuals, but to understand the NAT itself. Regarding the research methodology is conceptual in nature, not empirical, but draws on historical and sociological research on the subject. After noting that there is great divergence in the literature and in the media of how to understand the NAT established in the first chapter a minimum concept of 'atheism' and the second 'New Atheism'. In the last chapter, the third, we discuss some metatheses, general claims about the NAT. We conclude that atheism should be understood among other properties such as the absence of belief in God or the gods. The NAT even if not defined, it can be understood as a group of theses with family resemblance. Finally, in relation to metatheses, partially agree with Zenk that NAT is a media construction; LeDrew also with a social movement that is fundamentally an ideology. However, we disagree with Paine and Nall that such a move is a fundamentalism as defined by both authors. We hope that this work is a contribution to the study of atheism in our country.